The Degree of Possessing Soft Skills by Amman Governorate Basic School Teachers from their Perspectives - Tamimi, Rola Raafat; Al-Momani, Jihad Ali (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed at revealing the degree of soft skills that primary school teachers had from their point of view, according to these variables (gender, experience and sector). The study sample consisted of (335) primary school teachers chosen randomly in the Directorate of Education of General Markah in the province of Amman. The study followed the descriptive approach. For the sake of the study, a 40-item was developed to investigate eight soft skills; the questionnaire was checked in terms of its validity and reliability. The results showed that the teachers had statistically significant differences of soft skills from their perspective. Communication skill. Besides, the results also showed statistically significant differences in the degree of possession of all soft skills except the communication skill to the experience in favor of teachers who had five years of experience or more. In addition, the results also showed statistically significant differences in the degree of possession of all soft skills (communication, problem-solving, leadership, setting goals and time management) to the teacher's sector in favor of teachers who worked in private schools. Finally not lastly, the results didn't show any significant differences in the degree of possession of the soft skills (problem-solving, teamwork, setting goals and time management) to gender and in the soft skills (team working, lifelong learning and critical thinking) to the teacher's sector, in light of the results of the study, several recommendations were recommended, most notably the development of training plans and programs to improve the level of soft skills among teachers, and the ministry of education's interest in introducing soft skills into the curriculum.
Keywords: Soft Skills; Basic School Teachers; Amman Capital